Sales Volume and Production Costs Against Company Revenue: A Case Study in the Indonesia Stock Exchange 2014-2018 - Asep Effendi (Institute of Computer Science (IOCS), 2020)
The increase in the era of globalization has a direct impact on various sectors that support human life, including the business world, the rapid development of technology and communication also has an impact on increasingly fierce competition and faster changes in the business environment. As we know, one of the goals of the company is to make a profit. With these profits the company can grow and develop with greater capabilities. In fact, profit is a general goal of a company. This study aims to determine whether sales volume and production costs affect profits in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2014-2018. The problem that occurs is the increase or decrease in sales volume and production costs on profits in the food and beverage sub-sector companies. The method used is descriptive analysis and verification with a quantitative approach. The population in this study were 5 companies with a sample of 40 financial statements. The sampling technique used in this research is purposive sampling with certain criteria. The analytical method used is multiple linear regression analysis. The results of hypothesis testing in this study indicate that (1) sales volume has an effect on profit with a positive directional relationship, and (2) production costs have an effect on profit with a negative directional relationship.